2020
DOI: 10.1186/s13006-020-00297-6
|View full text |Cite
|
Sign up to set email alerts
|

How much can Mexican healthcare providers learn about breastfeeding through a semi-virtual training? A propensity score matching analysis

Abstract: Background: Mexico has shown a worrisome decrease in breastfeeding indicators, especially in the lowest socioeconomic level. Improving breastfeeding protection, promotion, and support services through workforce development is a key area of intervention. The objective of this study is to assess the influence on breastfeeding knowledge and abilities of a semi-virtual training for primary healthcare providers assisting beneficiaries of PROSPERA in Mexico, which is one of the largest conditional cash-transfer prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 21 publications
2
5
0
9
Order By: Relevance
“…The efficacy of online courses has been shown to be equal [ 60 ] if not greater [ 61 ] than live instruction for improving health professional knowledge in a range of countries, including in rural areas in high income countries [ 62 ]. Specifically for breastfeeding training, a study in Mexico showed that a hybrid online/face-to-face model may be best to increase staff knowledge [ 63 ]—though further research is needed in other regions. Given that global internet penetration continues to increase rapidly, we recommend that hospitals, if feasible, move to a mix of online and in-person modalities.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of online courses has been shown to be equal [ 60 ] if not greater [ 61 ] than live instruction for improving health professional knowledge in a range of countries, including in rural areas in high income countries [ 62 ]. Specifically for breastfeeding training, a study in Mexico showed that a hybrid online/face-to-face model may be best to increase staff knowledge [ 63 ]—though further research is needed in other regions. Given that global internet penetration continues to increase rapidly, we recommend that hospitals, if feasible, move to a mix of online and in-person modalities.…”
Section: Discussionmentioning
confidence: 99%
“…According to Mexico's National Health and Nutrition Survey, the prevalence of exclusive breastfeedingamong children under 6 months was 14.4% in 2012, indicating a decrease in what was reported in 2006 (22.3%). 14 Poverty is an important determinant of health and nutrition. In 2016, 20.7 million Mexican children and adolescents were poor; children under 5 years of age were the most affected by extreme poverty.…”
Section: Breastfeeding In México: a General Overviewmentioning
confidence: 99%
“…Which highlights the need for in-service training to improve breastfeeding knowledge and skills in health professionals. 14,17 This could justify the recommendation proposed by an expert committee in Mexico on the need to increase the coverage and quality of breastfeeding in-service training of health professionals to address the serious breastfeeding situation in the country. 14,17 Breastfeeding is one of the main affordable and modifiable maternal health interventions that protect against infant stunting.…”
Section: Breastfeeding In México: a General Overviewmentioning
confidence: 99%
“…Embasamento teórico/prático incipiente dos profissionais sobre aleitamento materno na APS Estudos indicaram preparo insuficiente sobre aleitamento materno na graduação e pósgraduação, [22][23] falta de ações de educação em saúde, 24 treinamentos, 25 e capacitações durante a trajetória desses profissionais nos serviços de saúde, 22,26 e insegurança e falta de habilidade dos profissionais de enfermagem para a tomada de decisão relacionada ao aleitamento materno. 22,[27][28] Demonstrou-se lacunas de conhecimento em consequência às fragilidades no embasamento teórico/prático dos profissionais de enfermagem. 29 Cuidado limitado voltado ao aleitamento materno na APS Nessa subcategoria, fragilidades foram associadas ao olhar biologicista, 29 à utilização de discurso autocrático, de culpabilização, com falta de diálogo, 26 uso de censura, proibição e postura prescritiva dos profissionais de enfermagem frente às mães.…”
Section: Métodounclassified